Laparoscopic repair of vesicovaginal fistula - Otsuka, Rodrigo Artur Pereira [UNESP]; Amaro, João Luiz [UNESP]; Tanaka, Milton Tatsuo; Epacagnan, Eduardo; Mendes Jr., José Barbosa; Kawano, Paulo Roberto [UNESP]; Fugita, Oscar Eduardo Hidetoshi [UNESP] (SAGE Publications, 2008)
Purpose: Vesicovaginal fistula (VVF) is one of the most devastating surgical complications that can occur in women. The primary cause remains an abdominal hysterectomy. Approach to this condition can be transvaginal or transabdominal. Laparoscopic repair of VVF may be an alternative approach to this treating rare condition. We present seven cases of VVF treated with transperitoneal laparoscopic technique and our results. Methods: We retrospectively reviewed the charts of 7 women ranging from 37 to 74 years in age (mean age 52.8 years) at our institution who underwent laparoscopic transperitoneal repair of VVF between February 2004 and March 2006. Etiology of the VVF, surgical technique, operative time, length of hospital stay, and complications were reviewed. Results: Six of the seven VVFs we repaired laparoscopically resulted from gynecologic procedures, and one patient presented with a VVF after a ureterolithotripsy. Mean operative time ranged from 130 to 420 minutes (mean 280 minutes), and mean hospital stay was 7 days. In one patient conversion to open surgery was necessary due to prolonged operative time. Two complications occurred a urinary tract infection in one patient and an inferior limb compartment syndrome in another. Conclusion: Transvaginal laparoscopic repair of VVF is feasible and safe and provides excellent results. It is a good alternative to the abdominal approach. However, advanced laparoscopic skills are mandatory. © 2008 Mary Ann Liebert, Inc.
Keywords: adult; aged; clinical article; compartment syndrome; cystovaginal fistula; female; gynecologic surgery; hospitalization; human; laparoscopic surgery; lithotripsy; postoperative complication; priority journal; retrospective study; surgical technique; transperitoneal laparoscopy; treatment duration; ureterolithotripsy; urinary tract infection; Adult; Aged; Female; Humans; Laparoscopy; Middle Aged; Retrospective Studies; Treatment Outcome; Vesicovaginal Fistula